2015
DOI: 10.1002/2014ja020710
|View full text |Cite
|
Sign up to set email alerts
|

Opposite hemispheric asymmetries during the ionospheric storm of 29–31 August 2004

Abstract: By making use of multiple ground-based and spaceborne instruments, we study ionospheric and thermospheric behavior during the moderately intense geomagnetic storm of 29-31 August 2004 (minimum Dst excursion of À128 nT). Although this storm was far from the strongest in solar cycle 23, it provoked quite interesting effects in the ionosphere, such as opposite hemispheric asymmetries in the ionospheric F layer and in the topside ionosphere and a development of the ionospheric superfountain effect in the postsunse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 80 publications
(173 reference statements)
3
38
0
Order By: Relevance
“…At the same time, the in situ plasma density decreased as compared to the previous dayside profile from SWA. One can also notice an increase in the VTEC and Ne at high latitudes in the southern hemisphere, which can be attributed to traveling ionospheric disturbances (TIDs) or to storm enhanced density (SED) occurring due to energy deposition at high latitudes and the consequent heating of the high-latitude atmosphere (e.g., Prölss 1995;Foster et al 2005;Astafyeva et al 2015a). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the in situ plasma density decreased as compared to the previous dayside profile from SWA. One can also notice an increase in the VTEC and Ne at high latitudes in the southern hemisphere, which can be attributed to traveling ionospheric disturbances (TIDs) or to storm enhanced density (SED) occurring due to energy deposition at high latitudes and the consequent heating of the high-latitude atmosphere (e.g., Prölss 1995;Foster et al 2005;Astafyeva et al 2015a). …”
Section: Resultsmentioning
confidence: 99%
“…However, in the topside region the positive disturbances can be led by an ionospheric uplift to higher altitudes where the recombination is slower. Previously, Astafyeva et al (2015a) observed the positive ionospheric disturbance in the topside ionosphere in the summer hemisphere that was explained by a combination of the storm-time PPEF and the enhanced storm-time thermospheric circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each observatory, the recovery phase is found to be noticeably long (more than 10 days). Dissimilarities between Figures 5a and 5b are likely due to the fact that F layer and topside ionosphere may not respond in the same way to a solar event [see, e.g., Yizengaw et al, 2006;Astafyeva et al, 2015a]. These plots are produced considering both vTEC and electron density data in the longitudinal range between 90°E and 135°E.…”
Section: Magnetic Data 221 Ground-based Magnetometersmentioning
confidence: 99%
“…There is overwhelming evidence in literature that perturbation neutral winds develop very slowly that shall change the prevailing dynamo at midlatitude causing disturbance dynamo (Blanc & Richmond, 1980) and when they reach the low latitudes with fresh nitrogen, they change O/N 2 ratio. (Ercha et al, 2012;Astafyeva, Zakharenkova, & Doornbos, 2015;Pancheva et al, 2016;Yiğit et al, 2016;Luo et al, 2016). Also, hemispheric asymmetry at low latitudes has been observed during later phases of the storms, mostly found due to the disturbance dynamo effect and O/N 2 changes.…”
Section: Resultsmentioning
confidence: 94%